The application of web 2.0 tools to determine receptive skills among Malay learners of Arabic language at the Universiti Sultan Zainal Abidin (UniSZA) / Aliyu Abdullahi ... [et al.] - Abdullahi, Aliyu; Mohmad Rouyan, Nurazan; Mohd Noor, Siti Salwa; Bashir, Ibrahim (2018)
The application of modern technologies in educational fields thrills with a sudden shift in using of the internet from Web 1.0 to Web 2.0 in the early 21st century. In the time various technological tools and social media sites evolved for social, and educational purposes. The application of such technological tools in teaching and learning of a language is termed computer-assisted language learning. This study aims to determine the performance of Malay undergraduate learners of Arabic as a foreign language at the universiti Sultan Zainal Abidin in reading, and listening skills using the online tool "QuizCreator". The sample of the study comprises 30 Malay Undergraduate students that are learning Arabic as a foreign language at UniSZA. The data of the study were collected through test instrument designed and marked based on TOAFL (AL-ARABIA) marking scheme. The results indicated that only seven participants scored pass mark in reading skill test while seven participants scored pass mark in listening skill test. This result is supported by various empirical researches conducted at different levels and time, with different methods. This study recommends the use of web 2.0 tools in teaching and learning of Arabic language to the learners.